Moral Analysis in the Videos of English Fairy Tales Channel and Its Relevance to Narrative Text Learning in Senior High School - Rizka Fitriani; I Putu Ngurah Wage Myartawan; I Nyoman Pasek Hadi Saputra (AL-ISHLAH: Jurnal Pendidikan, 2021)
This study analyzes the moral values of legends and fairy tales on the English Fairy Tales YouTube channel and examines its relevance to narrative text learning in schools. The approach used is qualitative research, with descriptive type. The sample videos taken from the English Fairy Tales channel are five videos. According to theory, analysis of moral values is carried out by looking at video samples and describing them. In contrast, relevance analysis will be carried out by reviewing the applicable learning syllabus. The research found that the videos analyzed contain values always to be grateful to God, care for others, be diligent, be brave, help each other, keep promises, and never give up. In addition, the moral values found in legends and fairy tales on the English Fairy Tales YouTube channel have relevance to the teaching of narrative texts in class X of Senior High School because the moral values contained in legends and fairy tales on the English Fairy Tales YouTube channel can support the use of English Fairy Tales channel videos as learning media that is in line with the learning competence.